Before and after: millet cultivation and the transformation of prehistoric crop production in northern Germany. (26th October 2018) - Filipović, Dragana; Meadows, John; Wiethold, Julian; Jahns, Susanne; Bittmann, Felix; Kirleis, Wiebke
Abstract : Abstract : A programme of radiocarbon dating aims to correlate the onset of millet cultivation in northern Germany with cultural and technological changes during the Bronze Age.